1996
DOI: 10.1021/jp961590j
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Wavelength Dependence of Energy Transfer and Charge Separation in Reaction Centers from Rhodobacter sphaeroides:  Evidence for Adiabatic Electron Transfer

Abstract: Femtosecond transient absorption spectroscopy has been used to investigate the excitation wavelength dependence of energy transfer and initial charge separation processes in reaction centers of the purple nonsulfur photosynthetic bacterium Rhodobacter sphaeroides (R-26) at room temperature. The Q Y transition bands of the bacteriopheophytins (H), bacteriochlorophyll monomers (B), and special pair (P) were selectively excited with pulses of 150 fs duration and 5 nm spectral bandwidth. Absorbance changes were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
143
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(168 citation statements)
references
References 63 publications
24
143
1
Order By: Relevance
“…sphaeroides RCs of the YM210W mutant (23,24), of the heterodimer and of the wild type (Van Brederode et al, unpublished observations), we added a parallel B* f P + B L -path with a rate of 1/ps. Such a process would then also be consistent with the observed 15% decrease of P* emission upon 800 nm excitation (relative to 860 nm excitation) measured at room temperature (20). The SADS of this target analysis ( Figure 7) were similar to those from Figure 6, except for an increase of the P*-stimulated emission and changes of the presumed P* and P + B L -bands in the 800 nm region.…”
Section: Target Analysis Of the Wt Rc Data With A Branched Reaction Ssupporting
confidence: 83%
See 1 more Smart Citation
“…sphaeroides RCs of the YM210W mutant (23,24), of the heterodimer and of the wild type (Van Brederode et al, unpublished observations), we added a parallel B* f P + B L -path with a rate of 1/ps. Such a process would then also be consistent with the observed 15% decrease of P* emission upon 800 nm excitation (relative to 860 nm excitation) measured at room temperature (20). The SADS of this target analysis ( Figure 7) were similar to those from Figure 6, except for an increase of the P*-stimulated emission and changes of the presumed P* and P + B L -bands in the 800 nm region.…”
Section: Target Analysis Of the Wt Rc Data With A Branched Reaction Ssupporting
confidence: 83%
“…On the basis of the time-gated spectra directly after the 0.2 ps ultrafast B* relaxation process we suggested that in this electron transfer pathway P + B L -and B + H L -are directly formed from B* which are then converted to P + H L -. Similar electron transfer mechanisms might be operating in wild type RCs at room temperature, as was suggested by (20) on the basis of 15-20% less P* stimulated emission formed upon excitation in the H and B band compared to excitation of the P band.…”
supporting
confidence: 56%
“…These observations have led a number of authors to suggest that primary charge separation might occur differently in PSII, potentially initiated by excitation of B A rather than P A /P B . A number of groups have shown in bacterial reaction centers that it is possible to observe, under certain conditions, the formation of radical pair states upon direct excitation of B A (69,128,130,142). Dekker & van Grondelle (24) and Rutherford and coworkers (98,99) have suggested that in PSII the lack of spectral differentiation and the orientation of 3 P, respectively, might be consistent with a contribution of B * A to primary radical formation.…”
Section: Pheomentioning
confidence: 99%
“…Contributions to complex kinetic profiles from dynamic effects involving motions of the chromophores, the protein, or both accompanying or following the decay of P* or P + H L -also have been discussed. 18,22,65,74,[104][105][106][107] In our previous work, we proposed the scheme for D LL given in Figure 2B, wherein the charge-separated intermediates (states other than P + Q A -and P + Q B -) lie above P* in free energy. This scheme derived from (1) the current view of the free energies of the intermediates in wild type, (2) the measured P/P + potential in D LL being at least 100 meV higher than in wild type, and (3) the lack of spectral signatures for formation of a chargeseparated state from P* in D LL at 295 K. In the simplest interpretation, the data presented here for D LL in either Deriphat glass or LDAO glass at 77 K are similar to the results for D LL at 295 K and can be reconciled with the model shown in Figure 2B, namely, with the charge-separated intermediates lying above P* and P* f ground state (via internal conversion) being the only decay route of P*.…”
Section: Heterogeneous-rc Model For D Llmentioning
confidence: 99%